Limbic encephalitis and antibodies to Ma2: a paraneoplastic presentation of breast cancer. Issue 2 (1st August 2000) - Sutton, Ian; Winer, John; Rowlands, David; Dalmau, Josep
Abstract : A patient with atypical medullary breast cancer is described who presented with symptoms of limbic encephalitis. The patient's serum and CSF contained antibodies that reacted with the nervous system and the tumour. These antibodies recognised Ma2, a neuronal protein related to paraneoplastic limbic and brainstem encephalitis in men with testicular tumours. This report highlights the importance of testing for paraneoplastic antineuronal antibodies in cases of unexplained limbic encephalitis and suggests screening for breast cancer in women with antibodies predominantly directed to Ma2.